Formulasi Sediaan Gel Rektal Ketoprofen dengan Peningkat Kelarutan Tween 80 - Sulfia Imami; Lucia Hendriati; Teguh Widodo (Jurnal Farmasi Sains dan Terapan, 2019)
Ketoprofen is a non steroidal anti-inflammatory drugs,often used as a post operative analgesic for the patient which is oral drug delivery, so ketoprofen should be formulated in rectal gel dosage forms that their therapeutic effect can be achieved quickly and has a low solubility. Tween 80 is a surfactant that is used to improve the solubility of ketoprofen. The purposes of this study were to determine the effect of Tween 80 on the release of ketoprofen and the physical quality of rectal gel. Evaluation of physical quality of the preparation includes organoleptic test, homogeneity test, spreadability test, viscosity test and pH test. The release of ketoprofen determined by Franz diffusion cell using whatman membrane 0.45μm and a solution of pH 7.4 phosphate buffer as receptor media. The amount of ketoprofen pass in through the membrane was determined by UV-VIS spectrophotometer. The results showed that the release profile of ketoprofen was affected by the concentration of Tween 80, the greater the concentration of Tween 80 the greater the value of flux release. Tween 80 at the concentration 1%, 2.5%, 5%, 7.5% to produce release flux values of 111.660; 155.465; 449.648; 644.853μg/cm2/hour1/2. Statistical analysis by Anova of difference release flux values of each formula were significantly different (p